2013
DOI: 10.1063/1.4804310
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrogen on the regeneration of boron-oxygen related defects in crystalline silicon

Abstract: When exposed to light, boron doped monocrystalline Czochralski grown silicon suffers from degradation of the minority carrier lifetime due to the formation of recombination active boron-oxygen related defects. The so called regeneration procedure is able to convert these recombination active defects into a new less recombination active state characterized by a higher minority charge carrier lifetime and stability under illumination. However, the exact working principle on microscopic scale is still unknown eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(72 citation statements)
references
References 16 publications
(27 reference statements)
3
68
1
Order By: Relevance
“…Whereas rates for annealing, degradation and probably destabilization only depend on temperature under typical regeneration conditions, regenera tion can be accelerated by increasing illumination intensity. In addition, the regeneration rate can be increased by improved hydrogenation of the silicon bulk [ 14) and according to Section 3 the ratio of hydrogen being in a favorable bonding state. Altogether, temperature, injection level, and hydrogen will deter mine which transition reactions dominate, and thus what is the occupation probability of the different 80 states in long term equilibrium…”
Section: High-speed Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas rates for annealing, degradation and probably destabilization only depend on temperature under typical regeneration conditions, regenera tion can be accelerated by increasing illumination intensity. In addition, the regeneration rate can be increased by improved hydrogenation of the silicon bulk [ 14) and according to Section 3 the ratio of hydrogen being in a favorable bonding state. Altogether, temperature, injection level, and hydrogen will deter mine which transition reactions dominate, and thus what is the occupation probability of the different 80 states in long term equilibrium…”
Section: High-speed Regenerationmentioning
confidence: 99%
“…by choosing suitable hydrogenated dielectric surface coatings [14,15] and optimized high temperature steps during sample processing [16,17] the regeneration process becomes faster. This leads to the idea that regeneration of BO related defects might in fact evolve from their passivation by hydrogen [14]. But the question arises how hydrogen can influence regeneration, even though it should mainly exist in bound states at typical regeneration temperatures of below 200 1C [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But more data is needed to investigate a possible additional influence of phosphorus or gallium on the regeneration of BO defects. This question will be addressed in a separate publication [32).…”
Section: Resultsmentioning
confidence: 99%
“…Wilking et al [103] and Walter et al [104] showed that the firing step mainly responsible for contact formation has a significant impact on the kinetics of passivation most probably as it determines the degree of hydrogenation of the silicon bulk. Also, it was observed that increasing the hydrogen content in dielectric layers can lead to an increase in the hydrogen concentration within the silicon, which correlates well with an acceleration of the passivation [102,103,[105][106][107][108].…”
Section: Role Of Hydrogenmentioning
confidence: 99%